Pleiepersonalets selvrapporterte evaluering av opplæring i ergonomisk forflytning, bruk av teknikker og hjelpemidler i en kommune - en longitudinell pilotstudie - Bente Nordtug; Karin Torvik; Jorunn Bjerkan; Nanna Hellesø; Hildfrid Vikkelsmo Brataas (Septentrio Academic Publishing, 2019)
Healthcare workers' self-reported evaluation of ergonomic transfer training, use of techniques and aids in a municipality - a longitudinal pilot study Healthcare workers' self-reported evaluation of ergonomic transfer training, use of techniques and aids in a municipality - a longitudinal pilot. Traditionally, healthcare work in nursing homes is regarded as physically strenuous work with a risk of back injuries stemming from adverse movement techniques. The purpose of the study was to analyse healthcare workers' self-reported evaluation of ergonomic transfer training in a municipality in Norway. The training aimed to improve healthcare personnel's ergonomic patient handling. N = 73 health care employees from a nursing home and homes to the disabled. Mean response rate during the three points of measurement was 77 %. Data were collected by questionnaire at baseline, at the end of the training, at 18 months, and 36 months after baseline. Then the data were compared using quantitative analysis at group level. Participants reported adequate training, improved availability of transferrelated resources, and increased use of transfer techniques over the course of the measurement periods. Respondents who asked transfer experts for guidance used transfer techniques more than others did.